House’s functional-pragmatic model of translation assessment and implications for evaluating English-Vietnamese translation quality - Thủy, Phạm Thị (VNU Journal of Foreign Studies; Vol 29 No 1, 2013)
Abstract: Translation quality assessment is not an undisputed issue in translation studies. The main problem seems to reside in how to assess the quality or what measures should be used to evaluate the translation. The measures used will be different, depending on the purpose of the assessment and on the theoretical framework applied to assessing the translation quality. This paper first discusses different models of translation quality assessment (TQA). Secondly, it describes House’s functional-pragmatic TQA model in details and applications of House’s model combined with quantitative methods in evaluating English- German translations. Thirdly, it draws out some implications for research into assessing English-Vietnamese translations. Keywords : models of translation quality assessment, functional – pragmatic model, cultural filter, register, genre, qualitative & quantitative analyses.